Dampak Pembangunan Jalan Tol Bali Mandara Terhadap Ekosistem Mangrove di Teluk Benoa Bali - Ida Bagus Made Baskara Andika; Cecep Kusmana; I Wayan Nurjaya (Graduate School Bogor Agricultural University (SPs IPB), 2019)
Ngurah Rai Forest Park, is one of the remaining mangrove ecosystems located in the Benoa Bali Bay, Indonesia. Ecosystem in this forest park is threathened due to the construction of Bali Mandara Highway. This study was conducted to determine the impact of the construction of the Bali Mandara Highway to the mangrove ecosystem in Ngurah Rai Forest Park. In this study, qualitative method was applied in order to compare the environmental parameter of mangrove ecosystem before and after construction of the highway. The construction of the Bali Mandara Highway affects several physical parameters of the mangrove ecosystem. The salinity, pH value and DO content are physical parameters which decreasing after the contruction. The decreasing also identified for current velocity, during the high tide current velocity decline to 0 - 0.44 m/s while during the low tide it goes down to 0 - 0.84 m/s. On the other hand, sedimentation area increases by 485.62 ha which causes silting. The vegetation analysis shows that Bali Mandara Highway has no significant impact to the diversity of mangrove species in Ngurah Rai Forest Park. Sonneratia alba still dominate the mangrove vegetation in those area.